Կրկին «Հաճախապատում ճառերի» հեղինակի ու թվագրման հարցի շուրջ, Աբրահամ Տերյանի մի հրատարակության առթիվ - Սահակյան, Դավիթ սրկ. (Մատենադարան)
Traditionally, the Oft-repeated Discourses (Yachakhapatum Chaṛek‘) was ascribed to St. Gregory the it was either one of the "second-generation" students of St. Mesrop or someone who lived even later. Abraham Teryan’s Moralia et Ascetica Armeniaca: The Oft- Repeated Discourses is the most recent work to address this question. Illuminator, because his name appears in the titles of all extant manuscripts, and several medieval sources including the History of Agathangelos confirm this attribution. Since the 19th century, many scholars have stated that the author of the "Oftrepeated Discourses" was St. Mesrop Mashtots‘. This view is based on a testimony of St. Koriwn that St. Mesrop wrote "oft-repeated discourses", as well as on the fact that the nature and content of the extant discourses, particularly the biblical references and many examples are significant evidence for the date of the author. Other scholars opine that neither St. Gregory nor St. Mesrop was the author of the Oft-Repeated Discourses; rather, By comparing Terian’s persuasive study with prior scholarly work, examining all his arguments and providing some new ones, the author concludes that there is no sufficient basis for asserting that St. Gregory the Illuminator or St. Mesrop Mashtots‘ were the authors of the Oft-repeated Discourses. He is more inclined to maintain that the extant discourses were compiled (if not written) most likely in the 6th century by an unknown compiler (author), and that later they were revised again. Традиционно автором “Многовещательных речей” считался св. Григорий Просветитель. Его имя вписано в заголовках всех сохранившихся рукописей, об этом свидетельствует в своей “Истории” Агафангел и другие средневековые авторы. Начиная с XIX века среди ученых распространилось мнение о том, что автор “Многовещательных речей” – св. Месроп Маштоц. Оно основано на свидетельстве св. Корюна, гласящем, что св. Месроп написал “часто произносимые речи”, а также на том, что характер и содержание дошедших до нас “речей” (в частности, использованные автором библейские цитаты и множество приведенных примеров), позволяют судить о времени жизни их автора. Другие ученые считают, что ни св. Григорий, ни св. Месроп не были авторами “Многовещательных речей”. По их мнению, автор – либо один из учеников второго поколения св. Месропа, либо некто, живший еще позднее. Этого же мнения придерживается Абраам Терьян, недавно также высказав- шийся по данному вопросу (Moralia et Ascetica Armeniaca: The Oft-Repeated Discourses). Автор, соглашаясь с доводами А.Терьяна, дополняет их новыми и склоня- ется к тому, что “Многовещательне речи” были составлены скорее всего в VI веке неизвестным автором, но затем были еще раз переработаны.
Keywords: Բանասիրություն